Climate change impacts on water security in global drylands - Stringer, LC; Mirzabaev, A; Benjaminsen, TA; Harris, RMB; Jafari, M; Lissner, TK; Stevens, N; Tirado-von der Pahlen, C (Cell Press, 2021)
Water scarcity affects 1-2 billion people globally, most of whom live in drylands. Under projected climate change, millions more people will be living under conditions of severe water stress in the coming decades. This review examines observed and projected climate change impacts on water security across the world’s drylands to the year 2100. We find that efficient water management, technology and infrastructure, and better demand and supply management, can offer more equitable access to water resources. People are already adapting but need to be supported with coherent system-oriented policies and institutions that situate water security at their core, in line with the components of Integrated Water Resources Management. Dryland water governance urgently needs to better account for synergies and trade-offs between water security and other dimensions of sustainable development, to support an equitable approach in which no one gets left behind.